Attendance rates and characteristics of women with obesity referred to the dietitian for individual weight management advice during pregnancy. (21st February 2020) - Porteous, Helen; de Jersey, Susan; Palmer, Michelle
Abstract : Background: Engagement in services to support healthy weight management during pregnancy is poor. A better understanding of those who attend is important in supporting women to participate in preventative health services. Aims: This retrospective observational study aimed to report attendance rates of pregnant women with obesity (body mass index (BMI) ≥ 30 kg/m 2 ) referred to a dietitian between 2012 and 2018 for weight management and describe who was referred and attended. Materials and Methods: Demographic, attendance and medical data for women with obesity who were either referred to a dietitian or were not referred were sourced from hospital data. Chi‐squared and t ‐tests were used to compare groups. Binary logistic regression analysis was used to identify characteristics associated with attendance within the referred group. Results: Of 5426 eligible women, 523 were referred to the dietitian, and 4903 women were not referred (Total sample: 29 ± 6 years, 39.0 ± 2.1 weeks gestation at birth). Referred women self‐reported a 6.7 kg/m 2 higher pre‐pregnancy BMI, 7% more were subsequently diagnosed with gestational diabetes mellitus (GDM), and 9% more were induced ( P  < 0.001) indicating a higher risk of adverse outcomes. Referred women attended a median (range) of 2 (0–8) appointments. The majority (78%) attended ≥1 appointment, and 41% attended ≥3 appointments. Women referred by a midwife (65%) or diagnosed with GDM were 1.9 and 3.0 times more likely to attend, respectively ( P  < 0.01). Being a smoker was negatively associated with attendance (odds ratio 0.388, P  < 0.001). Conclusions: Pregnant women with obesity referred for dietetic weight management appear at higher risk of adverse outcomes, with most attending ≥1 appointment. Engaging midwives in promoting referrals may increase attendance.